Hepatic arterial infusion chemotherapy (HAIC) plus Lenvatinib and PD-1 inhibitors versus systemic chemotherapy for unresectable intrahepatic cholangiocarcinoma - Qingyu Xu; Chendong Wang; Ran You; Bin Leng; Zeyu Yu; Ya Lu; Lingfeng Diao; Hao Jiang; Bei Wu; Guowen Yin (Discover Oncology)
Abstract Background Unresectable intrahepatic cholangiocarcinoma (iCCA) is characterized with dismal prognosis. Here, this study aimed to compare the efficacy and safety of hepatic arterial infusion chemotherapy (HAIC) combined with lenvatinib and PD-1 inhibitors versus systemic chemotherapy (SC) for unresectable iCCA. Methods Patients with histologically confirmed unresectable iCCA from January 2020 to December 2022 at our center were retrospectively enrolled. Propensity score matching (PSM) method was used to balance clinicopathological information between two groups. The primary endpoints were overall survival (OS), progression-free survival (PFS), whereas the secondary endpoints included objective response rate (ORR), disease-control rate (DCR) and safety profiles. Factors affecting the survival were identified through univariate and multivariate analyses. Results Eighty-six cases were included in this study. After PSM, there were 30 patients in each group. Compared to SC group, HAIC + Len + PD-1 inhibitor exhibited significantly improved OS (16.91 [95%CI: 11.6–28.4] months vs. 11.06 months [95%CI: 7.8–14.6 months], p = 0.011), PFS (11.17 months [95%CI: 7.0, 26.7] vs. 5.55 months [95%CI: 3.8, NA], p = 0.004), better ORR (56.7% vs. 23.3%, p = 0.008) and DCR (93.3% vs. 70.0%, p = 0.019). Multivariate analysis indicated that treatment arm of SC was a risk factor of worse OS and PFS, while uni-lobe tumor distribution, AST ≤ 40, CA19-9 level ≤ 39 were protective factors of worse OS. All adverse events were comparable and controllable between two groups. Conclusions In conclusion, HAIC combined with lenvatinib and PD-1 blockade yields better tumor control and survival outcomes over SC for unresectable iCCA, with manageable adverse events as well.